Matrix Metalloproteinases as Biomarkers for Ischemic Stroke: A Systematic Review - Putri Ulya Rachman; Juli, Cep; Yusuf Wibisono (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Ischemic stroke, a leading cause of mortality and disability worldwide, occurs due to the disruption of blood flow to the brain, resulting in neuronal damage and death. Matrix metalloproteinases (MMPs), a family of zinc-dependent endopeptidases, play a crucial role in the pathophysiology of ischemic stroke by degrading the extracellular matrix and contributing to blood-brain barrier disruption, inflammation, and neuronal cell death. This systematic review aims to comprehensively evaluate the current evidence regarding the potential of MMPs as biomarkers for ischemic stroke diagnosis, prognosis, and therapeutic monitoring. Methods: A systematic search of electronic databases (PubMed, Embase, and Cochrane Library) was conducted to identify relevant studies published between 2018 and 2024. Studies investigating the association between MMPs and ischemic stroke in human subjects were included. Data extraction and quality assessment were performed independently by two reviewers. Results: The search yielded 2,182 articles, of which 8 studies met the inclusion criteria. The included studies evaluated various MMPs, including MMP-2, MMP-3, MMP-9, and MMP-12, in different biological samples (serum, plasma, cerebrospinal fluid, and brain tissue) from ischemic stroke patients. The majority of studies reported elevated levels of MMPs in ischemic stroke patients compared to healthy controls, with MMP-9 being the most extensively studied. Furthermore, several studies demonstrated a correlation between MMP levels and stroke severity, functional outcome, and the risk of hemorrhagic transformation. Conclusion: The findings of this systematic review suggest that MMPs, particularly MMP-9, hold promise as potential biomarkers for ischemic stroke. However, further research is needed to validate their clinical utility and to explore their potential as therapeutic targets.